2011
DOI: 10.1186/1471-2164-12-73
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive mitochondrial genome of Calanoid copepod Calanus sinicus with multiple large non-coding regions and reshuffled gene order: Useful molecular markers for phylogenetic and population studies

Abstract: BackgroundCopepods are highly diverse and abundant, resulting in extensive ecological radiation in marine ecosystems. Calanus sinicus dominates continental shelf waters in the northwest Pacific Ocean and plays an important role in the local ecosystem by linking primary production to higher trophic levels. A lack of effective molecular markers has hindered phylogenetic and population genetic studies concerning copepods. As they are genome-level informative, mitochondrial DNA sequences can be used as markers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 85 publications
(127 reference statements)
4
43
1
Order By: Relevance
“…Recent study using concatenated twelve mitochondrial genes showed that Harpacticoida ( Tigriopus californicus ) was more closely related to Siphonostomatoida ( Lepeophtheirus salmonis and Caligus rogercresseyi ) than Calanoida ( Calanus sinicus ) (Fig. 2d) [23]. This mitochondrial phylogenetic hypothesis was generally congruent with the majority of the morphological phylogenies [5, 12, 13] except for the phylogenetic position of Poecilostomatoida (Fig.…”
Section: Introductionmentioning
confidence: 54%
“…Recent study using concatenated twelve mitochondrial genes showed that Harpacticoida ( Tigriopus californicus ) was more closely related to Siphonostomatoida ( Lepeophtheirus salmonis and Caligus rogercresseyi ) than Calanoida ( Calanus sinicus ) (Fig. 2d) [23]. This mitochondrial phylogenetic hypothesis was generally congruent with the majority of the morphological phylogenies [5, 12, 13] except for the phylogenetic position of Poecilostomatoida (Fig.…”
Section: Introductionmentioning
confidence: 54%
“…The PCR product, covering 1465 base pairs (bp) of the mitochondrial ND5 gene encoding the fifth subunit of the respiratory chain complex I (NADH dehydrogenase subunit 5), was obtained. This fragment was chosen based on the length of mitochondrial genes, their intermediate intra-and interspecies polymorphism in comparison to conserved CYTB, cytochrome oxidase subunit I (COI) and highly variable NADH dehydrogenase subunits 3 and 4 (ND3 and ND4) genes in the copepod subclass (Minxiao et al 2011).…”
Section: Dna Extraction and Amplificationmentioning
confidence: 99%
“…2; Jung et al 2006;Minxiao et al 2011). The most exceptional cases of mitochondrial variability documented to date are in the chaetognaths, Spadella cephaloptera and Sagitta elegans, for which natural populations exhibit unprecedented levels of intra-specific divergence (Marlétaz et al 2017).…”
Section: Genomic Resources For Marine Zooplanktonmentioning
confidence: 99%
“…Within the chaetognaths, mitogenomes are also very reduced compared to other metazoans, missing several common genes (Helfenbein et al 2004;Papillon et al 2004). On the other hand, the longest mitogenomes documented belong to the Copepods, up to 20 kb (Minxiao et al 2011). Several mitogenomes were found to contain multiple copies of some sequences (Ogoh and Ohmiya 2004;Burton et al 2007), or short tandem repeats, similar to microsatellites (Shen et al 2011). 19.2.3.4.…”
Section: Genomic Resources For Marine Zooplanktonmentioning
confidence: 99%